2021
DOI: 10.3390/su13042035
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Quality Aspects of Freeze-Drying Preceded by Traditional and Novel Pre-Treatment Methods as Exemplified by Red Bell Pepper

Abstract: Freeze-drying is one of the most expensive and most energy intensive processes applied in food technology. Therefore, there have been significant efforts to reduce the freeze-drying time and decrease its energy consumption. The aim of this work was to analyze the effect of pulsed electric field (PEF), ultrasound (US), and hybrid treatment (PEF-US) and compare them with the effect of blanching (BL) on the freeze-drying kinetics, energy consumption, greenhouse gasses emission, and physical quality of the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
1
16
4
Order By: Relevance
“…In the case of sonicated samples, slightly but significantly increased the water vapor adsorption capacity was observed, while for PEF-treated samples, hygroscopic properties did not significantly differ from untreated dried apples. These results are not in line with those of Rybak et al [59], who found that US and PEF employed before freezedrying resulted in an increase of about 42 to 48% in water-vapor adsorption ability. In turn, Zubernik et al [61] reported that air-dried apple adsorbed 2-3.5-times less water vapor when previously subjected to sonication in ethanol solution (up to 3 min), in comparison with dried untreated tissue.…”
Section: Dry Matter Water Activity Rehydration and Hygroscopic Propertiescontrasting
confidence: 99%
See 1 more Smart Citation
“…In the case of sonicated samples, slightly but significantly increased the water vapor adsorption capacity was observed, while for PEF-treated samples, hygroscopic properties did not significantly differ from untreated dried apples. These results are not in line with those of Rybak et al [59], who found that US and PEF employed before freezedrying resulted in an increase of about 42 to 48% in water-vapor adsorption ability. In turn, Zubernik et al [61] reported that air-dried apple adsorbed 2-3.5-times less water vapor when previously subjected to sonication in ethanol solution (up to 3 min), in comparison with dried untreated tissue.…”
Section: Dry Matter Water Activity Rehydration and Hygroscopic Propertiescontrasting
confidence: 99%
“…The possible explanation for these better rehydration properties is that electroporation phenomena caused tissue changes and increased the number of pores. Similar effect was also noticed for PEF-treated red bell pepper with prior freeze-drying [59]. As Parniakov et al [60] stated, PEF application effects shrinkage reduction during the drying process, preserving capillary structures, and affecting rehydration properties.…”
Section: Dry Matter Water Activity Rehydration and Hygroscopic Propertiessupporting
confidence: 64%
“…All samples were measured gravimetrically. About 0.6–1 g of the sample was placed in a dish and dried using the vacuum drying method (Memmert VO400, Schwabach, Germany) under a pressure of 10 mPa in 75 °C for 24 h and constant weight, according to information from Rybak et al [ 46 ] and the AOAC protocol [ 47 ]. Juices were placed on dried filter paper placed in a dish, which prevented the juice from burning.…”
Section: Methodsmentioning
confidence: 99%
“…For dry matter determination, the gravimetric method was used. About 0.6–1 g of juice was placed in a dish with filter paper; for powders, 1 g was placed into a dish without filter paper, and dried by vacuum drying method (Memmert VO400, Schwabach, Germany) under the pressure of 10 mPa in 75 °C for 24 h until constant weight, according to information from [ 2 , 52 ]. Measurements were made in triplicate.…”
Section: Methodsmentioning
confidence: 99%